International consensus on standard outcome measures for neurodevelopmental disorders: a consensus statement - Mulraney, Melissa; de Silva, Umanga; Joseph, Andria; Sousa Fialho, Maria da Luz; Dutia, Iain; Munro, Natalie; Payne, Jonathan M.; Banaschewski, Tobias; de Lima, Cláudia Bandeira; Bellgrove, Mark A.; Chamberlain, Samuel R.; Chan, Phyllis; et al. (JAMA network open, 2024)
The use of evidence-based standardized outcome measures is increasingly recognized as key to guiding clinical decision-making in mental health. Implementation of these measures into clinical practice has been hampered by lack of clarity on what to measure and how to do this in a reliable and standardized way.To develop a core set of outcome measures for specific neurodevelopmental disorders (NDDs), such as attention-deficit/hyperactivity disorder (ADHD), communication disorders, specific learning disorders, and motor disorders, that may be used across a range of geographic and cultural settings.An international working group composed of clinical and research experts and service users (n = 27) was convened to develop a standard core set of accessible, valid, and reliable outcome measures for children and adolescents with NDDs. The working group participated in 9 video conference calls and 8 surveys between March 1, 2021, and June 30, 2022. A modified Delphi approach defined the scope, outcomes, included measures, case-mix variables, and measurement time points. After development, the NDD set was distributed to professionals and service users for open review, feedback, and external validation.The final set recommends measuring 12 outcomes across 3 key domains: (1) core symptoms related to the diagnosis; (2) impact, functioning, and quality of life; and (3) common coexisting problems. The following 14 measures should be administered at least every 6 months to monitor these outcomes: ADHD Rating Scale 5, Vanderbilt ADHD Diagnostic Rating Scale, or Swanson, Nolan, and Pelham Rating Scale IV; Affective Reactivity Index; Children’s Communication Checklist 2; Colorado Learning Disabilities Questionnaire; Children’s Sleep Habits Questionnaire; Developmental-Disability Children’s Global Assessment Scale; Developmental Coordination Disorder Questionnaire; Family Strain Index; Intelligibility in Context Scale; Vineland Adaptive Behavior Scale or Repetitive Behavior Scale-Revised and Social Responsiveness Scale; Revised Child Anxiety and Depression Scales; and Yale Global Tic Severity Scale. The external review survey was completed by 32 professionals and 40 service users. The NDD set items were endorsed by more than 70% of professionals and service users in the open review survey.The NDD set covers outcomes of most concern to patients and caregivers. Use of the NDD set has the potential to improve clinical practice and research.